Model Predictive Control Design and Implementation on a 3x3 Model of Shell Heavy Oil Fractionator - Omar, Madiah (Universiti Teknologi PETRONAS, 2010)
Model Predictive Control (MPC) is the most famous advanced process control method in the industry. MPC refers to a class of computer control algorithms that utilize and explicit process model to predict the future response of the plant. Therefore, we can clearly see that this control strategy has brought a great importance for the industry to control the throughput to meet the requirement. For this purpose, a chemical process model is examined for set point tracking to measure its performance. Different direction of set point is tested for a given model, to measure optimum control horizon for the model and to study whether model is behaved efficiently for MIMO system. This study stated that given model is behaved efficiently for SISO system compared to MIMO system. This may due to modeling error in process gain